The crowdfunding platform as a tool for islamic social finance’s implementation (Journal of Economic Research & Business Administration, 2022)
Islamic social finance is becoming discussed direction, social financial tools of have been implementedfor poverty and hunger alleviation in society for more than a thousand years. While financialtechnology is one of the most important innovations developing at the swift-speed, partly driven byinformation technology and favorable regulation.The paper aims to research the role of financial technology in solving social challenges in the countrythrough Islamic social instruments. The authors have studied financial indicators and the effectiveness ofthe crowdfunding platform implementation for zakat collection. Nowadays, a lack of studies on Islamicsocial finance direction in academics increases the relevance of the article, which contains theoreticalaspects and provides practical recommendations for crowdfunding platform integration.The methodology of the study is based on the estimation of the crowdfunding platform’s financialplan, cash-flow revenue, and financial indicators for realistic and optimistic scenarios blockchain technologybased and without blockchain. The assessment of the Islamic finance social tools’ effectivenessdemonstrates, that the crowdfunding platform elaboration is effective for overcoming social challenges.Specifically, the authors explored the socio-economic effectiveness in the form of saving the state resourcesfor targeted social assistance to population. Furthermore, it was suggested, that crowdfundingplatform elaboration is the way for Islamic social finance promotion and financial technological advancementin the country.Key words: Islamic social finance, zakat, a crowdfunding platform, social effectiveness, financialtechnology.